Script and society - Boyes, Philip John. (Oxford)
viii, 308 sayfa
Keywords: “The Social Context of Writing Practices in Late Bronze Age Ugarit explores the social and cultural context of these complex writing traditions from the perspective of writing as a social practice. It combines archaeology, epigraphy, history and anthropology to present a highly interdisciplinary exploration of social questions relating to writing at the site, including matters of gender, ethnicity, status and other forms of identity, the relationship between writing and place, and the complex relationships between inscribed and uninscribed objects. This forms a case- study for a wider discussion of interdisciplinary approaches to the study of writing practices in the ancient world.” --